(3OQGSI GdeTJbGJ GdYQHjI h CKGQgG GdHdGZjI aj GdeYdbGJ GdYTQ GdLGgdj (B:s (3OQGSI EaQGOjI JMdjdjI h JQcjHjI (B/s - (3RHOI, HfYRhRs ((3GdLRGFQ (B:s (3GdeDSSI GdhWfjI ddcJGH ,s, 1989)
(3JMGhd gPg GdOQGSI GdeJhGVYI LhGfH ehVhY GdETJbGb h Pdc fXQG dGgejJg aj UjGZI GdcdGe GdYQHj h aVdg aj JfejI GddZI GdYQHjI h GJSGYgG h JcGKQ eaQOGJgG eeG LYd gPg GddZI LSeG MjG JJhdO GLRGDg h JJLOO UjZgcdeG JLOOJ GdGZQGV h GdeYGfj dPG aGf GdbGQjA SjLO GdJQcjR Ydi OQGSI GdeTJbGJ GdeSJNOeI aj GdbUGFO GdYTQ OQGSI Jbhe Ydi GdGMUGA h GdGSJbQGA Je GdJMdjdj h GdebGQfI h Pdc bUO GdhUhd Gdi eYQaI eOi GMJjGL GddZI h eTJbGJgGs
Keywords: (3GddZI GdYQHjIs